Kajian Etnohistoris - Mufti Riyani; Sukirno Sukirno; Elsy Sukria Fathin (Program Studi Pendidikan Sejarah - Universitas Samudra, 2018)
The Atjeh Religious Tourism Program is basically a program embodied by the Ministry of Tourism and Creative Economy program that wants Aceh to be projected as the World Islamic Tourism Indonesia. Aceh with unique local culture and wisdom is a potential area to run the Sharia tourism trend as a new tourist destination in the world today. However, this program experienced stagnation caused by concerns about the impacts that arose with the opening of tourism access in Aceh. Concerns and impacts that may arise basically can be anticipated by providing a comprehensive tourism concept and can work effectively to encourage government programs as well as to rebuild the Acehan culture which is actually beginning to erode. This paper aims to convey ideas that can be offered as a unique concept of gampong (village) based religious tourism with historical and cultural approaches to Acehan. This concept can lift Aceh from a religious, cultural, social and economic perspective in a comprehensive manner. This concept at the same time avoids the anxiety of the emergence of activities categorized as mushrik (associating partners with God) which occurs if religious tourism takes the object of a tomb or similar place while projecting a cosmopolitan Islam in front of the international world. The Integrated Tourism Village in question is gampong structuring by considering religious, cultural, social and economic aspects. Gampong Wisata contains historical tours, tourist attractions, arts, objects, customs, eating-drinking traditions, and Acehnese souvenirs. The idea of developing Integrated Tourism Village can be realized if there is good cooperation between the local government, the private sector (investors), and the community in the province of Aceh.